2012
DOI: 10.1007/s10528-012-9515-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Chitinase (Chit62) from Serratia marcescens B4A and Its Efficacy as a Bioshield Against Plant Fungal Pathogens

Abstract: Chitinases have been suggested to be involved in pathogen-antagonist interaction during biological control progress of plant pathogenic fungi. Here, a recombinant bacterial chitinase originally from Serratia marcescens B4A was produced, purified, and assayed biochemically to ascertain the activity and determine the kinetics parameters. Active enzyme was used to determine its biocontrol features against fungal phytopathogens. The results demonstrated that the optimum pH and temperature for the enzyme activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…Yong et al (2005) reported a V max value of 10.53 U min À1 mg À1 for a Sanguibacter sp. while Babashpour et al (2012) reported a V max value of 10.53 U for Serratia marcescens using colloidal chitin as substrate.…”
Section: Substrate Specificity and Kinetic Parametersmentioning
confidence: 98%
See 2 more Smart Citations
“…Yong et al (2005) reported a V max value of 10.53 U min À1 mg À1 for a Sanguibacter sp. while Babashpour et al (2012) reported a V max value of 10.53 U for Serratia marcescens using colloidal chitin as substrate.…”
Section: Substrate Specificity and Kinetic Parametersmentioning
confidence: 98%
“…In accordance with the activity staining results, the chitinase enzyme in the ammonium sulphate purified fraction showed a clear band by zymography, confirming that it was a chitinase. Molecular masses of bacterial chitinases generally range from 30 to 80 kDa (Annamalai et al, 2010;Margino et al, 2010;Babashpour et al, 2012;Jiang et al, 2012;Brzezinska et al, 2013;Dai et al, 2011). The purified enzyme was analysed by SDS-PAGE and activity staining of the gel (chitin zymography) shown in Fig.…”
Section: Gel Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…Since fungal cell walls and insect exoskeletons contain chitin, a homopolymer of β-1,4-linked N-acetyl-Dglucosamine residues as a major structural component, chitinases have been reported for their potential as biopesticides for the control of the plant diseases caused by various phytopathogenic fungi (3,4) and insect pests (1,5). Chitin is degraded into disaccharides and larger oligomeric saccharides by the action of chitinases (EC 3.2.1.14) through hydrolysis of the β-(1,4)-linkages (6), and these enzymes have been divided into 2 separate families, GH18 and GH19, based on amino acid sequences and their catalytic mechanisms (4).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that chitinases generated by Bt are involved in its antifungal activity and can enhance the insecticidal activity of Bt strains (7)(8)(9)(10). Many studies have reported the expression and application of chitinases in microorganisms (11)(12)(13)(14)(15). However, reports on the regulation mechanism of chitinase genes are scarce.…”
mentioning
confidence: 99%